Creative Thinking Processes: The Past and the Future. (12th December 2017) - Mumford, Michael D.; McIntosh, Tristan
Abstract: For more than one hundred years, students of creativity, including seminal efforts published in the Journal of Creative Behavior, have sought to identify the key processes people must execute to produce creative problem solutions. In recent years, we have seen a consensual model of key creative thinking processes being accepted by the field. In the present effort, we review the evidence bearing on the eight core processes proposed in this consensual model. Subsequently, directions for future research on creative thinking processes are discussed.